Is Fiscal Policy Coordination in EMU Desirable? - Beetsma, Roel.; Debrun, Xavier; Klaassen, Franc (Washington, D.C. : International Monetary Fund, 2001)
It is widely argued that Europe's unified monetary policy calls for international coordination at the fiscal level. We survey the issues involved in such coordination in the perspective of macroeconomic stabilization. A simple model identifies the circumstances under which coordination may be desirable. Coordination is beneficial when the cross-country correlation of the shocks is low. However, given the potentially adverse reaction by the ECB (as a result of free-riding or a conflict on the orientation of the policy mix), fiscal coordination is likely to prove counterproductive when demand or supply shocks are highly symmetric across countries and the governments are unable to acquire a strategic leadership position vis-a-vis the ECB.
Off-Campus Access: No User ID or Password Required
On-Campus Access: No User ID or Password Required
Mode of access: Internet